Constructive-Referential-Alternatism vis-a-vis G. E Moore’s Shift: A Case for a Direct Realist Ontological Account of Cognition - Isenyo Solomon Ogaba (Jurnal Office, 2021)
What necessitate the birth of this paper was the critical thinking that, is it possible for human beings (rational beings) to garner objective-unmediated knowledge of  the world in and around us? For the skeptic’s objective-unmediated knowledge is subject to doubt. While for the idealist the real (Genuine) knowledge is of the universal as it exists in the world forms (ideas). The materialist holds that real (genuine) knowledge is of matter. Contrary to this view, a direct realist account of cognition holds that, it is possible for rational beings (humans) to garner objective-unmediated knowledge of the world in an around us. As such, the identity theory of truth is used by the 20th century analytic philosopher George Edward Moore to  buttress his direct realist ontological account of cognition was used as a theoretical foundation for this work. Some findings of this paper are (1) There exists an external world (Physical world) (2) There exists a formal world where for example the principles of mathematics and physics exists (3) It is difficult to isomorphically reconcile the objective ontological statuses of both the external and formal world objects (4) That our claim to knowledge could either be a priori or a posteriori or both (5) That Moore’s direct realism is inadequate to account for human’s claim to know for certain all reality that exist. The research used documentary sources as its method of data collection. As such, the method adopted in this work is qualitative research design. However content analysis was used to analyze the data. Consequently, the paper made recommendations that;(1) there is need to embrace constructive-referential-alternatism in our knowledge claim,(2) there is need to also naturalize all epistemological account for the ontology of cognition in relation to a given consensual-contextual language domain. Hence, the role of language in the production and claim to knowledge cannot be overemphasized.